Development of UAV-based shot seeding device for rice planting - Liu, Wei; Zou, Shuaishuai; Xu, Xuelang; Gu, Qingyu; He, Weizhuo; Huang, Jun; Huang, Junhao; Lyu, Zichen; Lin, Jianqin; Zhou, Zhiyan; et al. (International Journal of Agricultural and Biological Engineering, 2022)
In order to realize the high-quality row seeding operation with unmanned aerial vehicle (UAV) in paddy field, a shot seeding device that can sow five rows of pelleted rice seeds at the same time was designed. The shot seeding device mainly consists of an external grooved wheel seed metering device and five shot seeding modules. The designed external grooved wheel seed metering device can take the seeds out of the seed box and divide the seeds into five parts. The shot seeding module can accelerate the pelleted rice seeds to reduce the impact of the UAV wind on the direction of seed movement. Furthermore, an angle adjustment mechanism for the shot seeding module was used to change the row spacing. The seed metering device test verified that when the speed of the seed metering wheel was 15 r/min, the coefficient of variation of the discharge rate of each row (C.V1) and total seed discharge rate stability (C.V2) were 1.70% and 1.04%, respectively. Image processing technique was used to test the UAV seeding performance. The distribution characteristics of seeds on the ground showed that the number of seeds in each row gradually increased from both sides to the middle in the width direction. According to the statistics, there were 60%-70% of the seeds in each row in the 100 mm width range. The field test showed that when the working height was 1.5 m and the seeding quantity was 38.56 kg/hm2, the performance of sowing in rows was obvious, the deviation rate of seeding quantity was 1.89%. After 16 d of sowing, the seeds’ emergence rate was stable, and the average emergence rate was 82.63% and the yield was 6775.50 kg/hm2. Keywords: unmanned aerial vehicle, rice direct seeding, row seeding, pelleted rice seeds DOI: 10.25165/j.ijabe.20221506.7301 Citation: Liu W, Zou S S, Xu X L, Gu Q Y, He W Z, Huang J, et al. Development of UAV-based shot seeding device for rice planting. Int J Agric & Biol Eng, 2022; 15(6): 1–7.